The Unwise Policy Of Community Based-Organisation: Can It Empower Them? Implementation Network Of Food Diversification In Indonesia - Kasmad, Rulinawaty; Samboteng, Lukman; Mahsyar, Abdul (Opción, 2019)
The main objective of this research is to develop the ability of Communi- ty-Based Organisations (CBOs) to implement food diversification policies. The research method used was the qualitative method. The data collection was carried out through discussions, namely interviews via the focus group discussion (FGD) technique, with a number of farmer women’s groups total- ling 20 groups, with 15 to 20 group members. The documentation of the in- formants was directly involved in carrying out these activities. The process of the data analysis included data reduction, data presentation, and completing the conclusions. The results of this study indicate that the implementation of policies implemented by the Dasawisma Women’s Farmer Group as a Com- munity-Based Organisation cannot effectively implement the policies therein. This is because the local government, as the initiator, does not facilitate them to carry out operational programs to empower them through the diversifica- tion of the consumption of local food crops.